Analisis Dukungan Sosial Dan Pengembangan Kualifikasi Diri Terhadap Adaptabilitas Karir Pada Wanita Karir Sudah Rumah Tangga Pada Karyawan Bank Bumn Wanita Yang Sudah Menikah Dikota Sukabumi - Hana Nurhasanah; Nor Norisanti; Resa Nurmala (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the effect of Social Support, and Self-Qualification Development on Career Adaptability partially and simultaneously. Respondents in this study were state-owned bank employees who were married, totaling 30 people. This research method uses quantitative methods with an associative approach. By carrying out the normality test, t test (partial) test f (simultaneous). The results in this study indicate a positive effect simultaneously between social support and development of self-qualification variables on career adaptability with the result that the calculated F value is greater than the F table where the calculated F value is 13,203> ​​F table is 3.40. Partially social support has a positive but not significant effect on career adaptability. This is evidenced by T count being greater than T table where the T count is 2.54 > T table 2.045. Qualifications for self-development have a positive but not significant effect on career adaptability. This is evidenced by T count being greater than T table where the T count is 2.956 > T table 2.054. Keywords : Social Support, Self-Qualification Development, Career Adaptability